PENGARUH PERMAINAN CLOTEH (CONGKLAK BATOK KELAPA BIJI TEH) DAN BERHITUNG SAMBIL BERCERITA TERHADAP KEMAMPUAN NUMERASI ANAK USIA DINI - Nuraeni, Eni; Apriyansyah, Chandra; Watini, Sri (Jurnal Manajemen Pendidikan, 2025)
This study aims to analyze the effect of Cloteh (Congklak made from coconut shells and tea seeds) and storytelling-based counting on early childhood numeracy skills, while also exploring their interaction based on gender. A quantitative approach with a 2×2 factorial experimental design was employed, involving 35 children aged 5–6 years at TK Plus Al-Adalah, Purwakarta Regency. The research instrument was a numeracy test covering indicators of number recognition, object counting, number-to-quantity matching, and pattern making. Data were analyzed using two-way ANOVA with additional simple effect tests. The results revealed that the Cloteh game was more effective than storytelling-based counting in improving numeracy skills, while the combination of both strategies produced the highest scores. Gender had no significant effect, although an interaction between learning media and gender was identified. The novelty of this study lies in the development of a culture-based numeracy learning model by integrating the traditional Cloteh game with storytelling-based counting, emphasizing the importance of contextual, engaging, and developmentally appropriate pedagogical strategies for early childhood numeracy.